Use of Preoperative Patient Reported Outcome Scores to Predict Outcome Following Autologous Chondrocyte Implantation - Howard, Jennifer Sebert (Orthop J Sports Med, 2014)
OBJECTIVES: Autologous chondrocyte implantation(ACI) has become an accepted treatment for articular cartilage defects; however, selection of appropriate patients in routine clinical practice remains challenging. The purpose of this study was to evaluate the use of preoperative patient reported outcome(PRO) scores in predicting postoperative self-reported global function following ACI with the goal of defining a minimum entry score that is predictive of a successful patient outcome. METHODS: A case series of patients a minimum of 1-year following ACI (n = 73, 27 female, age = 35 ± 7 yrs, BMI = 30 ± 5, mean defect = 7.4 ± 5.1 cm2, average follow-up = 2.3 ± 1.2 yrs) were evaluated. All patients were enrolled prospectively and completed PROs pre-surgery and 3, 6, and 12 months and annually post-surgery. As part of the ICRS Cartilage Injury Standard Evaluation Form, postoperatively patients were asked to rate their current function as “severely restricted in everything I do”, “restricted, many things are not possible”, “I can do nearly everything”, or “I can do everything”. Receiver operator curves (ROCs) were used to explore the discriminative accuracy of preoperative PROs (Total WOMAC Knee Score, IKDC Subjective Knee Form, and Lysholm Knee Scale) for identifying patients reporting to be able to do “nearly everything” or “everything” at the last available follow-up. From the ROCs cut-point scores for the values with the highest combined sensitivity and specificity were identified. Patients were then classified for each PRO instrument as having preoperative scores above or below the identified cut-point values. Cut-point status for preoperative WOMAC, IKDC, and Lysholm along with BMI, gender, age, defect area, and defect location (patellofemoral/tibiofemoral) were analyzed in a backwards entry logistic regression model to predict patients experiencing a positive outcome. RESULTS: Area under the curve was significantly greater than 0.5(range 0.80(IKDC)-0.82(Lysholm), p≤0.001) for each PRO ROC, demonstrating high accuracy in using preoperative PROs to predict post-operative function. The WOMAC score demonstrated a cut-point value of 34 with a sensitivity of 0.89 and specificity of 0.60 for identifying patients who went on to a positive outcome. For IKDC the cut-point was 35 (sensitivity=0.86, specificity=0.67). For Lysholm the cut-point was 41 (sensitivity =0.89, specificity=0.61). The only variables contributing to the final logistic model were IKDC score > 35 (p=0.002), and Lysholm score > 41 (p=0.002). The model demonstrated that those individuals with a preoperative IKDC score > 35 had 7.4 (95%CI: 2.1 - 26.9) greater odds of a positive outcome compared to those with an IKDC score ≤ 35 and those with a preoperative Lysholm score > 41 had 8.5 (2.2 - 33.2) greater odds of a positive outcome compared to those with a Lysholm score ≤ 41. Overall 85.5% of patients were correctly classified by the model as having a good or poor outcome. CONCLUSION: Pre-operative PROs can provide patients and physicians with accurate expectations for post-operative global levels of function. These results suggest that there may exist a minimum threshold of self-reported function for which ACI procedures can result in meaningful functional outcomes. Patients with functional levels below these cut-points should undergo preoperative interventions aimed at improving their function to above cut-point values and be counseled for realistic treatment expectations or available treatment alternatives.